The Impact Of Digitalization On Financial System Stability: Opportunities And Challenges - Selfia Putri Johana Eka Ningsih Simatupang; Vina Ramadhani Siregar; Imelda Krisdamayanti; Najma Azhira Lubis; Yolanda Widya Anggreni Situmorang; Dwita Sakuntala (Jurnal Ekonomi, 2025)
Digitalization has brought significant changes in various aspects of life, including the global financial system. This study aiming to analyze the impact of digitalization on the stability of the financial system by highlighting the opportunities and challenges that arise. This research method uses a qualitative approach with literature analysis from various international journals. The results of the study show that digitalization creates opportunities such as increased efficiency, financial inclusion, and transparency, but also presents challenges such US cyber risk, regulatory uncertainty, and market volatility. This study provides relevant insights for policy makers and financial industry players in facing the digital era. This study is expected to be a reference for understanding the role of digitalization in maintaining financial system stability.